The effect of Artificial Intelligence (AI) and Customer Experience (CX) use in telemedicine on customer satisfaction moderated by service duration - Lusitania Ayu Widyastuti; Rudy C. Tarumingkeng (Goodwood Publishing, 2025)
Purpose: This study investigates the effects of Artificial Intelligence (AI) use and Customer Experience (CX) in telemedicine services on customer satisfaction, with service duration as a moderating variable. Methods: A quantitative approach was applied using survey data from 121 active telemedicine users. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4, including measurement model evaluation, structural analysis, and moderation testing. Results: The results show that AI use has a positive but insignificant effect on customer satisfaction. In contrast, Customer Experience has a positive and significant effect on customer satisfaction, indicating its central role in telemedicine services. Service duration significantly and negatively moderates the relationship between AI use and customer satisfaction, suggesting that longer AI-based service processes reduce satisfaction. However, service duration does not significantly moderate the relationship between Customer Experience and customer satisfaction. Conclusion: Customer satisfaction in telemedicine is influenced more by experiential quality than by AI adoption alone. Effective AI implementation should emphasize service efficiency to enhance satisfaction. Limitation: This study is limited to a single telemedicine platform and uses a cross-sectional design, which may limit generalizability. Contribution: This research highlights the importance of Customer Experience and demonstrates the conditional effect of service duration on AI-driven telemedicine satisfaction.